Moving objects detection and tracking by omnidirectional sensors of a mobile robot : doctoral thesis - Marković, Ivan (I. Marković ; Fakultet elektrotehnike i računarstva, 2014)
ABSTRACT: In mobile robotics measurements from various sensors often yield direction-only information. In this thesis we develop directional statistics based methods for moving object tracking by omnidirectional sensors of a mobile robot. Firstly, the speaker localization problem is solved by modeling the measurements of a microphone array with a convex combination of von Mises distributions and the tracking is solved by Bayesian estimation based solely on the von Mises mixture. Furthermore, in the thesis we analyze the voice activity detection problem from the standpoint of model based voice activity detection methods which are enhanced by supervised learning algorithms. Considering the omnidirectional camera, spherical projection model coupled with displacement information from motor encoders is proposed to segment out static and dynamic features and movement tracking is performed on the sphere with a Bayesian filter based on the von Mises-Fisher distribution. Finally, fusion of heterogenous sensors for object tracking is analyzed in a comparative study of the extended information filter, the unscented information filter and the particle filter.